Some issues on innovation and innovation management policies in Vietnam - Nguyen Hoang Hai (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Over the years, “innovation” has gradually become synonymous with the development of countries, technological progress and the driving force leading to business success. Today, innovation is not simply recognized as “creating something new” but also a solution and a way to solve many problems in economic development, improving people’s quality of life and ensuring sustainable development goals. The term “innovation” is increasingly used by policymakers, marketing experts, and management consultants to imply more than just a strictly scientific concept but rather are decisions of government, political commitments or manifestos, a vision, a metaphor for a product or service that brings values ​​and positive meanings to people’s life. This article will provide some findings on the change in awareness and concept of innovation over the time and identify some contents that need to pay attention in the current government policy on management of innovation activities. Code: 22043001